Kegiatan Skrinning Tekanan Darah Dan Penyakit Hipertensi Pada Populasi Usia Produktif Di Sekolah SMA Kalam Kudus II, Kelurahan Duri Kosambi, Jakarta - Robert Kosasih; Muhammad Kharis Mahdaviqa; Nikita Tan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Hypertension is a condition where a person's blood pressure exceeds normal limits. In order to detect hypertension and provide health education, this community service activity evaluates the basic characteristics and blood pressure of men and women of productive age at Kalam Kudus II High School, Duri Kosambi Village, Jakarta. A total of 68 respondents participated, consisting of 26 men (38.2%) and 42 women (61.8%), with the majority being in the 18-35 year age group (52.9%). The results showed that 77.9% of respondents had normal systolic blood pressure and 82.4% had normal diastolic blood pressure. However, 22.1% of respondents experienced systolic hypertension and 17.6% experienced diastolic hypertension, with the highest prevalence in the 51-64 year age group. These findings emphasize the importance of early detection and health education about hypertension to prevent serious complications such as stroke and heart disease. Prevention can be done by changing lifestyle, such as exercising, avoiding smoking and alcohol, and consuming foods high in fiber and low in salt. Collaboration with schools and health units is very important for regular monitoring and comprehensive education. This community service activity aims to increase awareness and quality of life for individuals of productive age through prevention and early screening for hypertension.